Mathematics and cognition : a research synthesis by the International Group for the Psychology of Mathematics Education - Nesher, pearla; Kilpatrick, Jeremy; International Group for the Psychology of Mathematics Education (New York : Melbourne Sydney : Cambridge university press, 1990)
This book, which was first published in 1990, is the collaborative effort of a number of members of the International Group for the Psychology of Mathematics Education and primarily describes their work whilst at the same time covering many issues that interest researchers in mathematics education
Includes bibliographical references (p. 149-180).
Keywords: Mathematics. -- Study and teaching -- Psychological aspects